MANAGEMENT OF A CHILD WITH A DIFFERENCE IN SEX DEVELOPMENT CAUSED BY A NR5A1 PATHOGENIC VARIANT - Maria João Gaia; Jasna Šuput Omladič; Mojca Kavčič; Maruša Debeljak; Robert Kordič; Primož Kotnik (The Society for Children with Metabolic Disorders, 2023)
Introduction: Differences of Sex Development (DSD) occur in approximately 1/5000 live births. One of the recently found genetic causes for 46, xY DSD is NR5A1 gene variants, responsible for a broad phenotypic spectrum. Case Report: We present a case of a full-term newborn with ambiguous genitalia: one gonad located in the urogenital fold, the other inguinal, absence of wrinkling or hyperpigmentation of the urogenital folds' skin, the short genital tubercle, and labio-scrotal urethral meatus (External Genital Score of 4). Male-type urethra and the absence of a uterus or ovaries were determined by ultrasound. The karyotype was 46, xY, and a pathogenic heterozygous single nucleotide duplication 614dupC in the NR5A1 gene was found by NGS. The decided gender of rearing was male. Orchidopexy was performed at age 14 months. The histology of the gonad was indicative of a prepubertal testis. Discussion: NR5A1 variants have variable expressivity and incomplete penetrance. 46, xY patients with a pathogenic variant in the NR5A1 gene range from ambiguous genitalia to normal female external genitalia with virilization at puberty. Pubertal development does not strongly correlate to the degree of virilization at birth, with the majority showing signs of virilization at pubertal age.